Kombinasi Pupuk Kompos dan Pupuk Kimia terhadap Produksi Kedelai (Glycine max L.) - Ria Dwi Jayati; Yunita Wardianti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the effect of a combination of compost and chemical fertilizers on soybean (Glycine max L.) production. The research method used was a completely randomized design (CRD) using four treatments and six replications. The combination treatment of compost and chemical fertilizers, namely NPK fertilizer (control) (P0), straw compost + NPK (P1), coffee husk compost + NPK (P2) and vegetable waste compost + NPK (P3). The research data were analyzed by one factor ANOVA using SPSS 16 and continued by using the LSD test at the 5% real level. The results showed that the best treatment to increase the number of pods and dry weight of seeds was the P1 treatment (straw compost + NPK), but it was not significantly different from the P3 treatment (vegetable compost + NPK). In conclusion, there is an effect of a combination of compost and chemical fertilizers on soybean production (Glycine max L.). Keywords: Straw Compost, Coffee Husks, Vegetable Waste, NPK, Soybean Production